Current medical diagnosis & treatment 2014 - Papadakis, Maxine A.; McPhee, Stephen J.; Rabow, Michael W. (McGraw-Hill Medical, 2014)
Focusing on internal medicine, this book delivers coverage of more than 1,000 diseases and disorders. It offers insight into symptoms, signs, epidemiology, and treatment for these diseases and disorders. It places emphasis on the practical aspects of clinical diagnosis and patient management in various fields of internal medicine.